Preparation and Characterization of Organo-bentonites Modified by Different Surfactants - Zhou, Xiaojian; Wang, Xiaozhi; Jin, Cuili; Zhao, Bin; Yan, Feng; Feng, Ke (Asian Journal of Chemistry, 2012)
Clay minerals with 2:1 type structure possess prodigious area of inner-surface in silicate interlayers. Inserting surfactants into the interlayers will change the characteristics of inner-surface from hydrophilic to hydrophobic ones, which significantly enlarges the capacity of clay minerals to adsorb organic pollutants. Surfactants on the inner-surface of silicates can affect the physical and chemical properties of the inner-surface and the dimension of interspace. The array forms of the surfactant molecules on the inner-surface of minerals may also influence adsorption capacity to a special organic pollutant. In the present study four surfactants, cetyltrimethylammonium bromide (CTMAB), cetylpyridinium bromide (CPB), dodecyltrimethylammonium bromide (DTMAB) and dodecylpyridiniumbromide (DPB) were selected for production of organo-bentonite. With burning and X-radial diffraction (XRD) the amount of surfactants adsorbed on the inner-surface of bentonite were measured and the molecule array forms of surfactants on the inner-surface of bentonite were discussed. The results were as follows: (1) all surfactants tested could be adsorbed onto the inner-surface of bentonite, which increased the distance between layers of elemental cells; (2) for surfactants with same length of carbon chain, one with pyridinium head is more easily adsorbed on the inner-surface of bentonite than that with trimethylammonium; for surfactants with same head but different length of carbon chains, the one with greater length is more easily adsorbed onto inner-surface of bentonite; (3) The possible molecule array forms of cetyltrimethylammonium bromide and cetylpyridinium bromide, which possess carbon chain with 16 carbon atoms, was assumed to be a pseudo-trilayer lying on the inner-surface of bentonite and those for dodecyltrimethylammonium bromide and dodecylpyridiniumbromide, which possess carbon chain with 12 carbon atoms, were assumed to be a tightly-combined lateral bilayer; (4) with increasing concentration of surfactants the molecule array forms of surfactants on the inner-surface of bentonite became complex: monolayer ® lateral bilayer ® paraffin-type monolayer ® pseudo-trilayer.